Design, synthesis and biological activity of selective hCAs inhibitors based on 2-(benzylsulfinyl)benzoic acid scaffold. (1st January 2019) - Rotondi, Giulia; Guglielmi, Paolo; Carradori, Simone; Secci, Daniela; De Monte, Celeste; De Filippis, Barbara; Maccallini, Cristina; Amoroso, Rosa; Cirilli, Roberto; Akdemir, Atilla; Angeli, Andrea; Supuran, Claudiu T.
Abstract: A large library of derivatives based on the scaffold of 2-(benzylsulfinyl)benzoic acid were synthesised and tested as atypical inhibitors against four different isoforms of human carbonic anhydrase (hCA I, II, IX and XII, EC 4.2.1.1). The exploration of the chemical space around the main functional groups led to the discovery of selective hCA IX inhibitors in the micromolar/nanomolar range, thus establishing robust structure-activity relationships within this versatile scaffold. HPLC separation of some selected chiral compounds and biological evaluation of the corresponding enantiomers was performed along with molecular modelling studies on the most active derivatives.